WCS120 protein family and proteins soluble upon boiling in cold-acclimated winter wheat - Vítámvás, Pavel; Saalbach, Gerhard; Prásil, Iija Tom; Capková, Vera; Opatrná, Jana; Ahmed, Jahoor (Journal of plant physiology, 2007)
The amount of proteins soluble upon boiling (especially WCS120 proteins) and the ability to develop frost tolerance (FT) after cold acclimation was studied in two frost-tolerant winter wheat cultivars, Mironovskaya 808 and Bezostaya 1. Protein gel blot analysis, mass spectrometry (MS) and image analysis of two-dimensional gel electrophoresis (2-DE) gels were used to identify and/or quantify the differences in protein patterns before (non-acclimated, NA) and after 3 weeks of cold acclimation (CA) of the wheats, when FT increased from -4 degrees C (lethal temperature (LT(50)), for both cultivars) to -18.6 degrees C in Bezostaya 1 and -20.8 degrees C in Mironovskaya 808. Only WCS120 protein was visible in NA leaves while all five WCS120 proteins were induced in the CA leaves. Mironovskaya 808 had higher accumulation of three members of WCS120 proteins (WCS120, WCS66 and WCS40) than Bezostaya 1. MS analysis of total sample of proteins soluble upon boiling showed seven COR proteins in the CA samples and only three COR proteins in the NA samples of cultivar Mironovskaya 808 (MIR). In conclusion, the level of the accumulation of WCS120, WCS66 and WCS40 distinguished our two frost-tolerant winter wheat cultivars. Moreover, the differences of CA and NA samples of the MIR were shown by liquid chromatography (LC)-tandem mass spectrometry (MS/MS).
Keywords: Plant Proteins; aklimatizace; Triticum; nízká teplota; rozpustnost; DNA-Binding Proteins; Acclimatization; pšenice; multigenová rodina; rostlinné proteiny; DNA vazebné proteiny; vysoká teplota; Multigene Family; Hot Temperature; Cold Temperature; Solubility